A conceptual framework for supply chain modelling and simulation. (6th March 2007) - Jain, Sanjay
Modelling and simulation can be used for a wide range of supply chain management applications, but the models usually have to be custom developed with large effort. There is a need for an organised framework that can facilitate model development through identification of standard applications, the right level of abstraction, and associated requirements for data. This paper proposes such a framework utilising the industry standard Supply Chain Operational Reference (SCOR) model features for its major dimensions. Use of the framework will enable rapid development of models and hence increased use of simulation for supply chain applications.